Spiritual Tasks of Teachers in Higher Order Thinking Skills-Oriented Learning - Karim, Abdul; Hartati, Wiwi (International Journal of Psychosocial Rehabilitation, 2020)
-The 21st century learning has entered a disruption era. Such era demands the students gain more skill and effective learning to develop the knowledge. The teacher’s position in contemporary learning is as facilitator rather than as instructor in mediating subject matter. This study aims to analysis the spiritual task of teachers in Higher Order thinking skills (HOTS)-oriented learning in education. Accordance with the object, the sort of inquire about utilized in this inquire about is descriptive qualitative research. The data is collected by researchers from online indexed-articles that are displayed and published in websites. The subjective information were analyzed through triangulation, categorization, decrease, classification, and translation. The findings of this research is spiritual tasks of teachers’ learning of HOTS-oriented that are the roles of teachers’ meditation, the roles of teachers’ mediation, and the roles of teachers’ reflection in learning of HOTS-oriented.